2020
DOI: 10.1101/2020.09.01.20186049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

App-based symptom tracking to optimize SARS-CoV-2 testing strategy using machine learning

Abstract: Background: Tests are scarce resources, especially in low and middle-income countries, and the optimization of testing programs during a pandemic is critical for the effectiveness of the disease control. Hence, we aim to use the combination of symptoms to build a regression model as a screening tool to identify people and areas with a higher risk of SARS-CoV-2 infection to be prioritized for testing. Materials and Methods: We applied machine learning techniques and provided a visualization of potential region… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The results also show that the symptoms experienced by C19+ significantly differ, except for dyspnea, to those experienced by C19-. This agrees with other studies that also reported hyposmia, dysgeusia, and fever as significantly increased in C19+ persons [6,22,23]. Further, the large relative difference of hyposmia and dysgeusia frequencies for C19+ users suggests that hyposmia and dysgeusia are specific but not sensitive, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results also show that the symptoms experienced by C19+ significantly differ, except for dyspnea, to those experienced by C19-. This agrees with other studies that also reported hyposmia, dysgeusia, and fever as significantly increased in C19+ persons [6,22,23]. Further, the large relative difference of hyposmia and dysgeusia frequencies for C19+ users suggests that hyposmia and dysgeusia are specific but not sensitive, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The AUC of our predictor (0.74) is in the range of the performance of the symptom-based COVID-19 predictor described in the literature. Other reported AUCs were as 0.68 [22], 0.74 [2] and 0.90 [4]. The considerably higher AUC of the latter predictor is explained by the inclusion of many asymptomatic patients who did not report any contact with a COVID-19 infected person.…”
Section: Discussionmentioning
confidence: 92%
“…From the beginning of the pandemic until Nov 27, 2021, the region presented high rates of positive cases (7,852/100,000) and deaths (271/100,000)[ 9 ]. Since July 2020, a community broad testing strategy became available at the “Complexo da Maré” after an effort of civil society, non-governmental organizations (NGOs) and local community[ 10 ]. The testing was free of any charge and available on tents located in three different regions in Maré.…”
Section: Methodsmentioning
confidence: 99%
“…Dataset Specification. The most retrieved ML diagnosis models are based on signs and symptoms [19][20][21][22][23][24], followed by models based on laboratory tests [25,26]. Moreover, we found ML models based on clinical and electronic health records (EHRs) [27,28], ML models based on clinical reports [29], ML models based on image processing with other techniques [30,31], and ML models based on a combination of predictors including abnormal lab test results, the incidence rates, and signs and symptoms, as well as epidemiological features [32].…”
Section: Search Resultsmentioning
confidence: 99%